Profiling the nitrogen using YARA ALS Nitrogen Sensor tractor on young oil palm in share farm UiTM Jasin / Muhammad Nawab Hazim Mohd Azhan - Mohd Azhan, Muhammad Nawab Hazim (Faculty of Plantation and Agrotechnology, 2019)
Nitrogen is one of the macronutrient needed by all type of plants in order for them to growth into healthy plant. Nitrogen is also one of the important elements in plants because of its role in the chlorophyll production in the leaf. Plants will grow healthy if they receive sufficient amount of nitrogen needed. The study is conducted at Share Farm UiTM Jasin, Melaka. The YARA ALS N-Sensor is used to determine the Nitrogen needed by the young oil palm. The materials and method used is the tractor mounted N-sensor and the sensoroffice.com for the result. The result of visual analysis comes in a raster map form the sensor office website. There are 3 types of map that which are N recommendation Map, N as-applied Map and Relative biomass map. The map is interpreted by the colour on the map. For N recommendation map and N as-applied map, the darker the blue colour which consist of 16.7 % and 5.4 % of total area respectively indicates that the area have less N in the leaf while the lighter blue colour which consist of 6.0 % and 6.7 % of total area respectively indicates that the area have sufficient N in the leaf. As for the Relative biomass map, the darker green coloured area which consist 6.9 % of the total area indicates that the area have sufficient N while for the lighter coloured area which consist of 5.9 % of the total area indicates that the area has less N. The area which indicates the less N needs to be applied with N based fertilizer whereas the area with sufficient N did not have to apply fertilizer but needs to be monitored. The advantages of this study finding are that the farmers can know which area has less N and which area has sufficient N. This way the fertilizer application is efficient thus can reduce the cost and increase the profit.